2017
DOI: 10.1159/000478695
|View full text |Cite
|
Sign up to set email alerts
|

Group Composition and Monandry in Grizzled Langurs, Presbytis comata, on Java

Abstract: Grizzled langurs, Presbytis comata, a largely sexually monomorphic species, are reported to occur in populations where either the majority of groups comprise 1 adult male with 1 adult female, or where groups comprise 1 adult male with multiple females. As such, they may have a monandrous mating system. I investigated whether 1-male/1-female groups indeed form a significant part of the species' social system, and whether habitat variation (forest fragment size, distance to the forest edge, altitude) affects soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 54 publications
0
2
0
1
Order By: Relevance
“…The Endangered and largely arboreal grizzled langur is restricted to the western part of Java, where it is found from sea level up to 2500 m a.s.l. [44]. It is fully dependent on the last remaining patches of natural forest, but it still can come into conflict with humans there where the forest abuts the agroforests or forest plantations.…”
Section: Discussionmentioning
confidence: 99%
“…The Endangered and largely arboreal grizzled langur is restricted to the western part of Java, where it is found from sea level up to 2500 m a.s.l. [44]. It is fully dependent on the last remaining patches of natural forest, but it still can come into conflict with humans there where the forest abuts the agroforests or forest plantations.…”
Section: Discussionmentioning
confidence: 99%
“…Their work showed that more species were present on mainland Sumatra (6 rather than 3), that not P. potenziani from the Mentawai Islands but rather P. thomasi from northern Sumatra is the most basal species (contra, e.g. Brandon-Jones [1993]), that P. comata on Java [Nijman, 2017] is closely related to P. mitrata from Sumatra but not to P. thomasi or P. hosei from Borneo [contra, e.g. Chasen, 1940;Brandon-Jones, 1997] and that the Bornean endemic P. rubicunda is nested firmly in a group of Sumatran species, suggesting that only in the last 1.3 million years did they cross into Borneo.…”
Section: Introductionmentioning
confidence: 99%
“…Akan tetapi, sejauh ini, informasi yang tersedia sebagian besar masih tentang populasi surili di kawasan lindung karena banyaknya penelitian di kawasan tersebut (Heriyanto & Iskandar, 2004;Muhammad, 2016;Kusumanegara, Kartono, & Prasetyo, 2017;Widiana, Januari, Hasby, & Yuliawati, 2018;Handayani & Latifiana, 2019;Santosa, Rahmawati, & Utami, 2020;Eriska, 2021), demikian juga primata Colobine lainnya (Bismark, 2012;Ruskhanidar, Alikodra, Iskandar, Santoso, & Mansyoer, 2020). Terbatasnya informasi tentang surili di luar kawasan lindung (Nijman, 2017) telah menyulitkan program pelestarian dan konservasi populasi di kawasan tersebut (Doi & Takahara, 2016; Direktorat Jenderal Konservasi Sumberdaya Alam dan Ekosistem (Ditjen KSDAE), 2019).…”
Section: Dan Olehunclassified